Novel WFS1 mutations in patients with low-to-middle frequency hearing loss. (April 2023) - Guo, Luo; Gu, Xiaodong; Sun, Qin; Zhang, Yike; Li, Huawei; Du, Qiang
Abstract: Background: Hearing loss (HL) is the most common sensorineural disorder in human. It is estimated that genetic factors contribute to over 50% of prelingual hearing loss. Most of dominant HHL patients manifest postlingual progressive hearing loss that mainly affect high frequencies. However, mutations in a few dominant HL genes, such as WFS1, TECTA and DIAPH1, cause distinct audiogram that primarily affects the low and middle frequencies. Methods: We recruited twelve independent HL families with worse low or middle frequency audiograms. Each proband of these families was excluded for pathogenic mutations in GJB2, SLC26A4, and MT-RNR1 genes. Mutation screening was performed by whole exome sequencing. Next, candidate variants were validated in each family by sanger sequencing. Results: Six heterozygous WFS1 variants were identified in six families, including three novel mutations (c.2519T > G, p.F840C; c.2048T > G, p.M683R and c.2419A > C, p.S807R) and three previously reported variants (c.2005T > C, p.Y669H; c.2590G > A, p.E864K and c.G2389A, p.D797 N). All the novel mutations were absent in 100 ethnically matched controls and were predicted to be deleterious by multiple algorithms. Conclusions: We identified three novel and three previously reported WFS1 mutations in six unrelated Chinese families. Our findings enriched the genotype-phenotype spectrum of WFS1 related NSHL. Additional genotype-phenotype correlation study will clarify the detailed phenotypic range caused by WFS1 mutations.